Synthesis and Antiviral Evaluation of 1 '-Branched-5 '-Norcarbocyclic Adenosine Phosphonic Acid Analogues - Oh, Chang Hyun; Yoo, Kyung Ho; Hong, Joon Hee (WILEY-V C H VERLAG GMBH, 2010)
Novel 1'-methyl-5'-norcarbocyclic adenosine phosphonic acid analogues were synthesized using an acyclic stereo-selective route from commercially available 3,3-diethoxy-propan-1-ol 4. The synthesized nucleoside phosphonate 19 and phosphonic acid 21 were subjected to antiviral screening against various viruses.
Keywords: ANTI-HIV ACTIVITY; MODIFIED NUCLEOSIDE PHOSPHONATES; HERBICIDAL ACTIVITY; NUCLEOTIDES; DESIGN; 2' -C-CYANO-2' -DEOXY-1-BETA-D-ARABINOFURANOSYLCYTOSINE; 1-(3-C-ETHYNYL-BETA-D-RIBO-PENTOFURANOSYL)CYTOSINE; 2' -DEOXY-2' -METHYLIDENECYTIDINE; RIBONUCLEOSIDES; DERIVATIVES